On the characterization of ultra‐precise X‐ray optical components: advances and challenges in ex situ metrology. (1st September 2014) - Siewert, F.; Buchheim, J.; Zeschke, T.; Störmer, M.; Falkenberg, G.; Sankari, R.
<x xml:space="preserve">Abstract</x> To fully exploit the ultimate source properties of the next‐generation light sources, such as free‐electron lasers (FELs) and diffraction‐limited storage rings (DLSRs), the quality requirements for gratings and reflective synchrotron optics, especially mirrors, have significantly increased. These coherence‐preserving optical components for high‐brightness sources will feature nanoscopic shape accuracies over macroscopic length scales up to 1000 mm. To enable high efficiency in terms of photon flux, such optics will be coated with application‐tailored single or multilayer coatings. Advanced thin‐film fabrication of today enables the synthesis of layers on the sub‐nanometre precision level over a deposition length of up to 1500 mm. Specifically dedicated metrology instrumentation of comparable accuracy has been developed to characterize such optical elements. Second‐generation slope‐measuring profilers like the nanometre optical component measuring machine (NOM) at the BESSY‐II Optics laboratory allow the inspection of up to 1500 mm‐long reflective optical components with an accuracy better than 50 nrad r.m.s. Besides measuring the shape on top of the coated mirror, it is of particular interest to characterize the internal material properties of the mirror coating, which is the domain of X‐rays. Layer thickness, density and interface roughness of single and multilayer coatings are investigated by means of X‐ray reflectometry. In this publication recent achievements in the field of slope measuring metrology are shown and the characterization of different types of mirror coating demonstrated. Furthermore, upcoming challenges to the inspection of ultra‐precise optical components designed to be used in future FEL and DLSR beamlines are discussed.